Loss of samples in the tissue microarray technique: comparison between slides using adhesive tape and silanized slides - Lima, Flávio de Oliveira [UNESP]; Almeida, Joaquim Soares de; Costa, Henrique de Oliveira; Pinheiro, Nathanael F.; Oshima, Celina Tizuko; Franco, Marcello F. de [UNESP] (Maney Publishing, 2011)
The tissue microarray (TMA) technique allows multiple tissue samples in a single block. Commercial adhesive tape is used to avoid the loss of tissue samples during the immunostaining process. Few reports exist in the literature comparing the use of these adhesive tapes to other adhesive techniques. The objective of this study was to compare loss of sections adhered to slides using commercial adhesive tapes versus using silanized only slides. TMA was constructed with varying tissues using a fixed-base device (Beecher Instruments), placing 108 cylinders of 1 mm diameter in duplicate, spaced 1.2 mm apart. Section of 4 mu m were cut from the TMA block and adhered to 30 silanized slides and 30 commercial glass slides using adhesive tape, according to manufacturer's recommendations. Vimentin immunoexpression was evaluated by immunohistochemistry. Antigenic recovery was realized in citrate buffer using a microwave oven. Cylinder loss in the immunohistochemical process was quantified and expressed as: total (>80%), almost complete (75-79%), or partial (50-74%). The commercial adhesive tape group presented lesser total loss (1.1 versus 6.4%), almost complete loss (2.2 versus 3.5%), and partial loss (2.1 versus 3.8%) than the silanized slide group (ANOVA, P < 0.05). The sum of total and almost complete losses in the silanized slide group was 9.9%, greater than the losses in slides using commercial adhesive tapes (3.3%) and less than reported and considered acceptable in the literature (10-30%). In conclusion, the use of silanized only slides presents very satisfactory results, requires less training, and reduces costs significantly, thus justifying their use in research.
Keywords: Immunohistochemistry; Sample losses; Tissue microarray